Australian Historical Studies – New Directions for the Twenty-First Century - Damousi, Joy (History compass, 2003)
Australian Historical Studies is the oldest historical journal in Australia. It began in 1940 in the Department of History at the University of Melbourne. Since then, the journal has been the barometer of the state of the profession and the changing nature of historical scholarship in Australia. From its initial connections to British constitutional and imperial history, to the establishment of Australian history as a discipline in its own right, AHS has charted the various trends, fashions and orientations of Australian historians. The expansion of social then cultural history, the influence of the social movements of the 1960s and 1970s in the emergence of labour and feminist history, as well as other specialisations such as immigration, urban, military, and sport history have all been documented in the contributions received over the past thirty years. The journal has also reflected the changing face of the profession itself, with a growing number of female, Indigenous and non-Anglo contributors who have offered a corrective to the over-representation of white, male, and middle class scholars who initially dominated the ranks of the profession. As the number of historians who have been employed outside of the universities has increased in number, so too have the contributions from freelance historians, museum curators and archivists. It is a challenge for any editor to capture a broad audience when dealing with this level of fragmentation of the discipline and an increasing specialisation of fields of research. These areas of history have now expanded and diversified to the extent that they run their own journals, conferences, and seminars, often without reference to the work of others in related fields.